Attitudes of Interns and Graduates of the Faculty of Dentistry at Libyan International Medical University Towards the OSCE Exam - Amel Alawami; Asiel Shembeish; Yousef Saleh; Mahmoud Faraj (AlQalam Journal of Medical and Applied Sciences, 2025)
An OSCE can be defined as an assessment tool that is standardized and based on simulation to comprehensively measure candidates’ cognitive, psychomotor, and practical clinical skills. It is, in fact, a structured station examination unit where several students can display their clinical performances using the same material. This is a standard assessment tool for dental universities. Objective Structural Clinical Examinations (OSCEs) are widely used to evaluate clinical competence in dental education. The study assesses the perceptions of dental interns and graduates about the OSCE format at the Faculty of Dentistry-Libyan International Medical University (LIMU). The study used cross-sectional descriptive methodology to assess interns’ and dental graduates’ attitudes and perceptions toward the Objective Structured Clinical Examination (OSCE). The total sample size was 180, but it was reduced to 130 after evaluation. The dental interns and graduates completed the structured online questionnaire outlining a mixed survey program on attitudes toward the goal, the number of stations, and the time allocation for the overall OSCE program. A total of 77 dental interns and graduates gave an approving nod to the objectivity of an OSCE in assessing clinical knowledge. Similarly, 74 believed that increasing the number of stations is beneficial for a holistic evaluation. However, it reported the most significant concerns regarding the OSCE’s ability for students to point out strengths and weaknesses in practical skills and the relevance of the written questions. Only 11 interns and graduates of dentistry expressed discontent with the time allocated per station. This study has demonstrated both the merits and challenges of OSCE in dental education. Although the OSCE is acknowledged to be an objective evaluation, there were concerns regarding stress, time-boundedness, and the inability of this evaluation to mimic everyday clinical situations fully.